A solid particle continuous casting protective slag and a preparation method and application thereof

By combining composite binders and disc granulation technology with vibration-assisted technology, a solid granular protective slag with low porosity and high strength was prepared, which solved the defects of powdery and ordinary granular protective slags and improved the stability and efficiency of the steel continuous casting process.

CN122099248APending Publication Date: 2026-05-29GUIZHOU ACADEMY OF TESTING & ANALYSIS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610172018.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-02-06
Publication Date
2026-05-29

AI Technical Summary

Technical Problem

Existing powdered and ordinary granular protective slags have problems such as dust pollution, uneven composition, uneven melting, low mechanical strength and high porosity in the continuous casting process of steel. Traditional granulation processes are difficult to meet the requirements of high density and uniformity.

Method used

By employing a composite binder formulation and an improved disc granulation process, solid granular protective slag with low porosity and high mechanical strength is prepared through multi-stage granulation and vibration-assisted technology. This process includes the mixed use of starch paste, sodium carboxymethyl cellulose, and polyvinyl alcohol, as well as the combination of a disc granulator and mechanical vibration.

Benefits of technology

It achieves solid particles with low porosity (<5%), high mechanical strength (>20N/particle), and stable melting performance in protective slag, significantly reducing dust pollution, improving the surface quality of cast billets and continuous casting efficiency, and reducing the surface crack rate and inclusion adsorption efficiency of cast billets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122099248A_ABST
    Figure CN122099248A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a solid particle continuous casting protective slag and the preparation method and application of the solid particle continuous casting protective slag, wherein the preparation method comprises the following steps: mixing a protective slag base material with a composite binder; the composite binder comprises 0.5-1 wt% of a starch paste, 0.5-1.5 wt% of sodium carboxymethyl cellulose and 0.5-1 wt% of polyvinyl alcohol; multi-stage granulation is carried out by using a disc granulator; and the obtained particles are subjected to step-by-step drying to obtain the solid particle continuous casting protective slag with a moisture content meeting the requirement. The significant effect is that a composite binder system suitable for high-density protective slag is developed, and a vibration auxiliary technology is applied to disc granulation of the protective slag for the first time, an integrated continuous production process of granulation-densification-drying is realized, and the protective slag particles with low porosity, high mechanical strength and excellent melting uniformity are prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of auxiliary material processing technology for continuous casting in metallurgy, specifically to a solid granular protective slag for continuous casting, its preparation method, and its application. Background Technology

[0002] In the continuous casting process of steel, the mold flux is a functional material that covers the surface of molten steel. Its main functions are to prevent oxidation of the molten steel, adsorb non-metallic inclusions, lubricate the contact surface between the billet and the mold, and regulate heat transfer in the billet. The performance of the mold flux directly affects the stability of the continuous casting process, the surface quality of the billet, and production efficiency.

[0003] Currently, the widely used forms of protective slag in industry mainly include powdered protective slag and ordinary granular protective slag. Protective slag is composed of complex multi-component materials such as base materials (wollastonite, blast furnace slag, quartz sand, etc.), fluxes (sodium alkali, fluorite, sodium fluoride, manganese ore powder, etc.), and melting rate regulators (carbon black, etc.). However, they have the following technical defects in application: 1. Limitations of powdered protective slag: It is prone to dust and pollutes the environment: Powdered protective slag is prone to generating dust during transportation, storage and feeding, which not only wastes raw materials, but also deteriorates the production environment and endangers workers' health.

[0004] Severe component segregation: Due to the differences in density and particle size of different components (such as wollastonite, fluorite, lithium carbonate, etc.), the powdered protective slag is prone to stratification during the feeding process, resulting in uneven slag composition and affecting the metallurgical effect.

[0005] Uneven melting: When powdered protective slag melts on the surface of molten steel, it is easy to form local "hot spots" or "cold spots", which leads to fluctuations in the thickness of the liquid slag layer and affects the lubrication and heat transfer uniformity of the billet.

[0006] 2. Shortcomings of ordinary granular protective slag: High porosity (10%~20%): Particle protective slag prepared by traditional disc granulation or extrusion granulation processes is usually porous, which leads to: unstable melting rate: air in the pores expands rapidly at high temperature, causing particles to burst and affecting the uniformity of the slag layer.

[0007] Low mechanical strength (5~10 N / piece): It is easily broken during transportation and feeding, and will still generate some dust.

[0008] Component segregation not completely resolved: Although granulation reduces some dust problems, uneven component distribution may still occur if the internal structure of the particles is loose.

[0009] Continuous casting mold flux is an essential functional material in the steelmaking continuous casting process and a crucial material for ensuring the smooth casting of molten steel. In the mold, it primarily performs five functions: preventing steel oxidation, providing thermal insulation, absorbing and dissolving inclusions, lubricating the cast billet, and controlling heat transfer. Based on morphological characteristics, continuous casting mold flux can be classified into powdered flux, hollow granular flux, and solid granular flux. Powdered flux has disadvantages such as severe environmental pollution and unsuitability for automatic addition. Hollow spherical granular flux has a low specific gravity and good spreadability, making it suitable for mechanical addition. Therefore, hollow granular flux will become the main direction for the development of clean and intelligent production in continuous casting processes.

[0010] 3. Deficiencies of existing protective slag granulation processes: Wet granulation (such as spray drying): Although it can produce spherical particles, it consumes a lot of energy and the particles have low strength, making it difficult to meet the requirements for high density.

[0011] Dry extrusion granulation: The particles are irregular in shape and have microcracks inside, which affects the melting performance and lubrication effect of the protective slag.

[0012] Traditional disc granulation: The particles formed by direct water spraying have high porosity and cannot meet the requirements for high densification. Summary of the Invention

[0013] To address the shortcomings of existing technologies, the present invention aims to provide a solid granular continuous casting protective slag, its preparation method, and its application. Through a composite binder formulation and an improved disc granulation process, a solid granular protective slag with a porosity of <5%, high compressive strength, stable melting performance, and high density is successfully prepared. It can be widely used in the continuous casting production of high value-added steel grades and has significant industrial application value.

[0014] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention proposes a method for preparing solid granular continuous casting protective slag, the key of which includes the following steps: Step 1: Mix the protective slag base material with the composite binder; The composite binder comprises: 0.5-1 wt% starch paste, 0.5-1.5 wt% sodium carboxymethyl cellulose, and 0.5-1 wt% polyvinyl alcohol; Step 2: Perform multi-stage granulation using a disc granulator; Step 3: Perform step-by-step drying on the particles obtained in Step 2 to obtain solid particle continuous casting protective slag with the required moisture content.

[0015] Furthermore, the protective slag base material comprises 50-70 wt% wollastonite, 20-30 wt% blast furnace slag, 12-15 wt% fluorite, and the remainder being quartz sand.

[0016] Furthermore, the composite binder comprises 0.5-0.8 wt% starch paste, 1.5 wt% sodium carboxymethyl cellulose, and 0.8 wt% polyvinyl alcohol.

[0017] Furthermore, the specific process of multi-stage granulation using a disc granulator in step 2 is as follows: Pre-wetting stage: Disc tilt angle 40-45°, rotation speed 10-12 rpm, spray in 30% composite adhesive; Nucleus generation stage: Maintain an inclination angle of 45° and a rotation speed of 12-15 rpm to increase the particle diameter to 1-2 mm; Densification stage: Adjust the tilt angle to 50-55°, rotate the speed to 18-20 rpm, apply mechanical vibration at a frequency of 50-60 Hz simultaneously, and spray in the remaining composite adhesive.

[0018] Furthermore, the frequency of the mechanical vibration is 55Hz, and the diameter of the disc granulator is 2-3m.

[0019] Furthermore, the solid granular continuous casting protective slag has a porosity of <5% and a compressive strength of >20N / particle.

[0020] Furthermore, the solid granular continuous casting protective slag has a moisture content of <0.5%, a melting uniformity of ±1.5℃, and a dust generation of <0.1%.

[0021] Secondly, the present invention also proposes a system for preparing solid granular continuous casting protective slag for implementing the method described in the first aspect, comprising: A mixing device is used to mix the protective slag base material with a composite binder, said composite binder comprising: 0.5-1 wt% starch paste, 0.5-1.5 wt% sodium carboxymethyl cellulose, and 0.5-1 wt% polyvinyl alcohol; Disc granulators are used for multi-stage granulation of protective slag base materials with mixed composite binders; An auxiliary vibration device is used to provide mechanical vibration at a frequency of 50-60Hz during the granulation process of a disc granulator to assist in densification. Drying equipment is used to perform step drying on particles obtained by a disc granulator to obtain solid particle continuous casting protective slag with a moisture content that meets the requirements.

[0022] Thirdly, the present invention also proposes a solid granular continuous casting protective slag, which is prepared by the method described in the first aspect or by the preparation system described in the second aspect.

[0023] Fourthly, the present invention also proposes the application of a solid granular continuous casting protective slag prepared by the method described in the first aspect or the preparation system described in the second aspect, or the solid granular continuous casting protective slag described in the third aspect, in the steel continuous casting process.

[0024] The significant effects of this invention are: 1. This invention develops a composite binder system suitable for high-density protective slag and, for the first time, applies vibration-assisted technology to protective slag disc granulation, realizing an integrated continuous production process of granulation-densification-drying. Based on this production process, protective slag particles with low porosity (<5%), high mechanical strength (>20N / particle) and excellent melting uniformity are prepared. When the prepared protective slag particles are used in the continuous casting process of steel, due to their solid structure, heat conduction is more uniform, avoiding local overheating or incomplete melting, significantly reducing surface cracks of the billet, enabling the slag layer thickness fluctuation to be <0.5mm, reducing the surface crack rate of the billet by more than 60%, and improving the inclusion adsorption efficiency by 15%.

[0025] 2. The application of the protective slag particles of this invention in the continuous casting process of iron and steel has yielded the following advantages: (1) In terms of metallurgical performance: the thickness fluctuation of the liquid slag layer is <0.5mm; the surface crack rate of the billet is reduced by 60%; the adsorption efficiency of inclusions is increased by 15%; (2) Production process: Raw material utilization rate increased to 98%; continuous casting speed increased by 5-8%; crystallizer life extended by 20-30%.

[0026] 3. The solid granular continuous casting protective slag described in this invention not only has high mechanical strength and is not easily broken, but also reduces dust emissions by more than 80%, improving the workshop environment and reducing raw material loss; moreover, its spherical solid granular structure ensures better flowability than powdery slag, enabling automated and precise feeding and reducing human intervention errors; in addition, the viscosity of the liquid slag layer formed after the solid particles melt is stable, reducing the frictional resistance between the billet and the crystallizer and reducing the risk of sticking and leakage.

[0027] 4. Based on the above-mentioned advantages, the solid granular continuous casting protective slag of the present invention is particularly suitable for the continuous casting production of high value-added steel grades such as automotive steel sheets and silicon steel, and has significant industrial application value. Attached Figure Description

[0028] Figure 1 This is a flowchart of the preparation method described in this invention; Figure 2 This is a schematic diagram of the preparation system described in this invention; Figure 3 This is a schematic diagram of the structure of the disc granulator and the auxiliary vibration device; Figure 4 This is a schematic diagram of the particle size characteristic parameters of samples with different composite binder contents; Figure 5 These are SEM images of samples with different composite binder contents; Figure 6These are the OM diagrams of samples with different composite binder contents. Detailed Implementation

[0029] The specific embodiments and working principles of the present invention will be further described in detail below with reference to the accompanying drawings.

[0030] To address the shortcomings of existing powdered and ordinary granular protective slags, as well as the deficiencies in existing granulation processes, this invention develops a high-density, low-porosity solid granular continuous casting protective slag and optimizes its preparation process to achieve the following: reduced dust pollution and improved raw material utilization; increased particle strength (compressive strength > 20 N / particle) to ensure no breakage during transportation and feeding; optimized melting uniformity to stabilize the slag layer and improve the surface quality of the cast billet; reduced fluctuations in the continuous casting process, reduced defects such as steel leakage and cracks, and improved continuous casting efficiency.

[0031] This invention provides a novel preparation method using a composite binder formulation and an improved disc granulation process. This method successfully produces solid granular protective slag with a porosity of <5%, high compressive strength, and stable melting performance. It can be widely applied in the continuous casting production of high-value-added steel grades and has significant industrial application value. The process steps of the preparation method are as follows: Step 1: Mix the protective slag base material with the composite binder; The protective slag base material comprises 50-70 wt% wollastonite, 20-30 wt% blast furnace slag, 12-15 wt% fluorite, and the remainder being quartz sand. The composite binder comprises: 0.5-1 wt% starch paste, 0.5-1.5 wt% sodium carboxymethyl cellulose, and 0.5-1 wt% polyvinyl alcohol; Step 2: Perform multi-stage granulation using a disc granulator 20. Pre-wetting stage: Disc tilt angle 40-45°, rotation speed 10-12 rpm, spray in 30% composite adhesive; Nucleus generation stage: Maintain an inclination angle of 45° and a rotation speed of 12-15 rpm to increase the particle diameter to 1-2 mm; Densification stage: Adjust the tilt angle to 50-55°, rotate the speed to 18-20 rpm, apply mechanical vibration at a frequency of 50-60 Hz simultaneously, and spray in the remaining composite adhesive; Step 3: Perform step-by-step drying on the particles obtained in Step 2 to obtain solid particle continuous casting protective slag with the required moisture content.

[0032] Based on the preparation method described above, the present invention proposes the following embodiments: Example 1: like Figure 1 As shown in the figure, this embodiment proposes a method for preparing solid granular continuous casting protective slag, and the specific steps are as follows: Step 1: Mix the protective slag base material with the composite binder; The protective slag base material includes 53wt% wollastonite (80 mesh), 30wt% blast furnace slag (80 mesh), 12wt% fluorite (200 mesh), and 5wt% quartz sand (200 mesh). The specific surface areas of wollastonite particles (D50 = 14.57 μm) and blast furnace slag particles (D50 = 13.96 μm) in the protective slag base material are 377.9 and 387.7 m² / g, respectively. 90% of the wollastonite and blast furnace slag particles have diameters less than 41.02 and 40.34 μm, respectively (considering the different specific gravities of various raw materials, to ensure thorough mixing within a short time and improve slurry preparation capacity, the feed particle size should be as uniform and fine as possible, preferably less than 50 μm). Wollastonite powder exhibits irregular, unevenly sized elongated shapes, while blast furnace slag powder exhibits relatively uniform granular shapes. Compared to elongated wollastonite powder, granular blast furnace slag powder is more conducive to dispersion in solvents, thus facilitating the preparation of slurries with good dispersibility and stability.

[0033] To increase the particle size of the protective slag after spray granulation and improve its mechanical strength, conventional technologies typically use modified sodium carboxymethyl cellulose-II (CMC-II), modified sodium carboxymethyl cellulose-V (CMC-V), polyethylene glycol (PEG400), polyvinyl alcohol (PVA1788), polyvinyl butyral (PVB), corn starch, etc., as a single binder.

[0034] The present invention proposes a composite adhesive system with a specific ratio, wherein the composite adhesive comprises: 0.5 wt% starch paste, 1.5 wt% sodium carboxymethyl cellulose and 0.8 wt% polyvinyl alcohol, with the remainder being deionized water; The embodiments of this invention employ a ternary composite adhesive, the composition of which and its mechanism of action are as follows: Silica sol: enhances particle forming ability; Sodium carboxymethyl cellulose (CMC): Enhances wet particle strength; Polyvinyl alcohol (PVA): Improves particle toughness and prevents drying cracking.

[0035] Step 2: Multi-stage granulation is performed using a disc granulator 20 with a disc diameter of 3m. Pre-wetting stage: Disc tilt angle 40°, rotation speed 10 rpm, spray in 30% composite adhesive, spray volume 2L / min; Nucleus generation stage: Maintain an inclination angle of 45° and a rotation speed of 12 rpm to increase the particle diameter to 1-2 mm; Densification stage: Adjust the tilt angle to 50°, rotate at 18 rpm, apply mechanical vibration at a frequency of 50 Hz simultaneously, and spray in the remaining composite adhesive at a spray volume of 2 L / min.

[0036] Step 3: The particles obtained in Step 2 are dried in a stepwise manner to ensure the uniformity of the particle moisture content. First, dry at 80℃ for 30 minutes, then dry at 110℃ for 20 minutes to obtain solid particle continuous casting protective slag with a moisture content of 0.3%.

[0037] like Figure 2 As shown, this embodiment also proposes a system for preparing solid granular continuous casting protective slag to implement the aforementioned method, comprising: A mixing device is used to mix protective slag base material with composite binder; Disc granulator 20 is used for multi-stage granulation of protective slag base material of mixed composite binder. Disc granulator 20 has a multi-layer spray gun system 30 (e.g., Figure 3 As shown): The upper layer is sprayed with composite adhesive, and the lower layer is sprayed with water (particle size < 50 μm). The spraying ratio is dynamically adjusted by PLC. An auxiliary vibration device 10 is installed at the bottom of the disc granulator 20 to provide mechanical vibration at a frequency of 50Hz during the granulation process of the disc granulator 20, so as to promote the discharge of voids inside the particles, improve the uniformity of binder distribution, and enhance particle density. Drying equipment is used to perform step drying on the granules produced by the disc granulator 20 to obtain solid granules of continuous casting protective slag with sufficient moisture content.

[0038] The solid granular continuous casting protective slag was tested and found to have a porosity of 4.2% and a compressive strength of 23.7 N.

[0039] Example 2: like Figure 1 As shown in the figure, this embodiment proposes a method for preparing solid granular continuous casting protective slag, and the specific steps are as follows: Step 1: Mix the protective slag base material with the composite binder; The protective slag base material includes 63wt% wollastonite (80 mesh), 20wt% blast furnace slag (80 mesh), 13wt% fluorite (200 mesh), and 4wt% quartz sand (200 mesh). The composite binder comprises: 0.6 wt% starch paste, 0.5 wt% sodium carboxymethyl cellulose, and 0.5 wt% polyvinyl alcohol, with the remainder being deionized water; Step 2: Multi-stage granulation is performed using a disc granulator 20 with a disc diameter of 2m. Pre-wetting stage: Disc tilt angle 45°, rotation speed 12 rpm, spray in 30% composite adhesive; Nucleus generation stage: Maintain an inclination angle of 45° and a rotation speed of 15 rpm to increase the particle diameter to 1-2 mm; Densification stage: Adjust the tilt angle to 55°, rotate at 20 rpm, apply mechanical vibration at a frequency of 60 Hz simultaneously, and spray in the remaining composite adhesive.

[0040] Step 3: The particles obtained in Step 2 are dried in a stepwise manner, first at 80°C for 30 minutes, then at 110°C for 20 minutes, to obtain solid granular continuous casting protective slag with a moisture content of 0.38%.

[0041] like Figure 2 As shown, this embodiment also proposes a system for preparing solid granular continuous casting protective slag to implement the aforementioned method, comprising: A mixing device is used to mix protective slag base material with composite binder; Disc granulator 20 is used for multi-stage granulation of protective slag base material of mixed composite binder. Disc granulator 20 has a multi-layer spray gun system 30 (e.g., Figure 3 As shown): The upper layer is sprayed with composite adhesive, and the lower layer is sprayed with water (particle size < 50 μm). The spraying ratio is dynamically adjusted by PLC. An auxiliary vibration device 10 is installed at the bottom of the disc granulator 20 to provide mechanical vibration at a frequency of 60Hz during the granulation process of the disc granulator 20, so as to promote the discharge of voids inside the particles, improve the uniformity of binder distribution, and enhance particle density. Drying equipment is used to perform step drying on the granules produced by the disc granulator 20 to obtain solid granules of continuous casting protective slag with sufficient moisture content.

[0042] The solid granular continuous casting protective slag was tested and found to have a porosity of 4.3% and a compressive strength of 23.2 N.

[0043] Example 3: like Figure 1 As shown in the figure, this embodiment proposes a method for preparing solid granular continuous casting protective slag, and the specific steps are as follows: Step 1: Mix the protective slag base material with the composite binder; The protective slag base material includes 60wt% wollastonite (80 mesh), 25wt% blast furnace slag (80 mesh), 14wt% fluorite (200 mesh), and 1wt% quartz sand (200 mesh). The composite binder comprises: 0.7 wt% starch paste, 1.2 wt% sodium carboxymethyl cellulose, and 0.6 wt% polyvinyl alcohol, with the remainder being deionized water; Step 2: Multi-stage granulation is performed using a disc granulator 20 with a disc diameter of 2.5m. Pre-wetting stage: Disc tilt angle 40°, rotation speed 11 rpm, spray in 30% composite adhesive; Nucleus generation stage: Maintain an inclination angle of 45° and a rotation speed of 13 rpm to increase the particle diameter to 1-2 mm; Densification stage: Adjust the tilt angle to 50°, rotate at 19 rpm, apply mechanical vibration at a frequency of 55 Hz simultaneously, and spray in the remaining composite adhesive.

[0044] Step 3: The particles obtained in Step 2 are dried in a stepwise manner, first at 80°C for 30 minutes, then at 110°C for 20 minutes, to obtain solid granular continuous casting protective slag with a moisture content of 0.44%.

[0045] like Figure 2 As shown, this embodiment also proposes a system for preparing solid granular continuous casting protective slag to implement the aforementioned method, comprising: A mixing device is used to mix protective slag base material with composite binder; Disc granulator 20 is used for multi-stage granulation of protective slag base material of mixed composite binder. Disc granulator 20 has a multi-layer spray gun system 30 (e.g., Figure 3 As shown): The upper layer is sprayed with composite adhesive, and the lower layer is sprayed with water (particle size < 50 μm). The spraying ratio is dynamically adjusted by PLC. An auxiliary vibration device 10 is installed at the bottom of the disc granulator 20 to provide mechanical vibration at a frequency of 55Hz during the granulation process of the disc granulator 20, so as to promote the discharge of voids inside the particles, improve the uniformity of binder distribution, and enhance particle density. Drying equipment is used to perform step drying on the granules produced by the disc granulator 20 to obtain solid granules of continuous casting protective slag with sufficient moisture content.

[0046] The solid granular continuous casting protective slag was tested and found to have a porosity of 4.5% and a compressive strength of 21.8 N.

[0047] Example 4: like Figure 1 As shown in the figure, this embodiment proposes a method for preparing solid granular continuous casting protective slag, and the specific steps are as follows: Step 1: Mix the protective slag base material with the composite binder; The protective slag base material includes 56 wt% wollastonite (80 mesh), 27 wt% blast furnace slag (80 mesh), 15 wt% fluorite (200 mesh), and 2 wt% quartz sand (200 mesh). The composite binder comprises: 0.8 wt% starch paste, 1.2 wt% sodium carboxymethyl cellulose, and 0.7 wt% polyvinyl alcohol, with the remainder being deionized water; Step 2: Multi-stage granulation is performed using a disc granulator 20 with a disc diameter of 2m. Pre-wetting stage: Disc tilt angle 45°, rotation speed 10 rpm, spray in 30% composite adhesive; Nucleus generation stage: Maintain an inclination angle of 45° and a rotation speed of 14 rpm to increase the particle diameter to 1-2 mm; Densification stage: Adjust the tilt angle to 55°, rotate at 19 rpm, apply mechanical vibration at a frequency of 50 Hz simultaneously, and spray in the remaining composite adhesive.

[0048] Step 3: The particles obtained in Step 2 are dried in a stepwise manner, first at 80°C for 30 minutes, then at 110°C for 20 minutes, to obtain solid granular continuous casting protective slag with a moisture content of 0.46%.

[0049] like Figure 2 As shown, this embodiment also proposes a system for preparing solid granular continuous casting protective slag to implement the aforementioned method, comprising: A mixing device is used to mix protective slag base material with composite binder; Disc granulator 20 is used for multi-stage granulation of protective slag base material of mixed composite binder. Disc granulator 20 has a multi-layer spray gun system 30 (e.g., Figure 3 As shown): The upper layer is sprayed with composite adhesive, and the lower layer is sprayed with water (particle size < 50 μm). The spraying ratio is dynamically adjusted by PLC. An auxiliary vibration device 10 is installed at the bottom of the disc granulator 20 to provide mechanical vibration at a frequency of 50Hz during the granulation process of the disc granulator 20, so as to promote the discharge of voids inside the particles, improve the uniformity of binder distribution, and enhance particle density. Drying equipment is used to perform step drying on the granules produced by the disc granulator 20 to obtain solid granules of continuous casting protective slag with sufficient moisture content.

[0050] The solid granular continuous casting protective slag was tested and found to have a porosity of 3.9% and a compressive strength of 24.8 N.

[0051] Example 5: like Figure 1 As shown in the figure, this embodiment proposes a method for preparing solid granular continuous casting protective slag, and the specific steps are as follows: Step 1: Mix the protective slag base material with the composite binder; The protective slag base material includes 60wt% wollastonite (80 mesh), 23wt% blast furnace slag (80 mesh), 14wt% fluorite (200 mesh), and 3wt% quartz sand (200 mesh). The composite binder comprises: 1 wt% starch paste, 0.5 wt% sodium carboxymethyl cellulose, and 1 wt% polyvinyl alcohol, with the remainder being deionized water; Step 2: Multi-stage granulation is performed using a disc granulator 20 with a disc diameter of 3m. Pre-wetting stage: Disc tilt angle 45°, rotation speed 11 rpm, spray in 30% composite adhesive; Nucleus generation stage: Maintain an inclination angle of 45° and a rotation speed of 13 rpm to increase the particle diameter to 1-2 mm; Densification stage: Adjust the tilt angle to 55°, rotate at 20 rpm, apply mechanical vibration at a frequency of 60 Hz simultaneously, and spray in the remaining composite adhesive.

[0052] Step 3: The particles obtained in Step 2 are dried in a stepwise manner, first at 80°C for 30 minutes, then at 110°C for 20 minutes, to obtain solid granular continuous casting protective slag with a moisture content of 0.41%.

[0053] like Figure 2 As shown, this embodiment also proposes a system for preparing solid granular continuous casting protective slag to implement the aforementioned method, comprising: A mixing device is used to mix protective slag base material with composite binder; Disc granulator 20 is used for multi-stage granulation of protective slag base material of mixed composite binder. Disc granulator 20 has a multi-layer spray gun system 30 (e.g., Figure 3 As shown): The upper layer is sprayed with composite adhesive, and the lower layer is sprayed with water (particle size < 50 μm). The spraying ratio is dynamically adjusted by PLC. An auxiliary vibration device 10 is installed at the bottom of the disc granulator 20 to provide mechanical vibration at a frequency of 60Hz during the granulation process of the disc granulator 20, so as to promote the discharge of voids inside the particles, improve the uniformity of binder distribution, and enhance particle density. Drying equipment is used to perform step drying on the granules produced by the disc granulator 20 to obtain solid granules of continuous casting protective slag with sufficient moisture content.

[0054] The solid granular continuous casting protective slag was tested and found to have a porosity of 4.4% and a compressive strength of 22.7 N.

[0055] The performance indicators of the solid granular continuous casting protective slag prepared in various embodiments of the present invention and the traditional granular protective slag are compared as follows: In implementing this invention, solid particle continuous casting protective slag samples with different composite binder contents were selected and labeled as S0 (0% CMC), S1 (0.5% CMC), and S2 (1% CMC), respectively. The particle size distribution of the dried particle samples was tested using a laser particle size analyzer (model: Malvern Mastersizer 3000), with a test range of 0.1~1000 μm. Each sample was tested three times, and the average value was taken. The macroscopic morphology of the particles was observed using an optical microscope (OM, model: Olympus BX53); the microscopic morphology and cross-sectional structure of the particles were observed using a scanning electron microscope (SEM, model: Zeiss Sigma 300). Before testing, the samples were sputter-coated with gold, and the accelerating voltage was 15 kV. Phase composition analysis of the samples was performed using an X-ray diffractometer (XRD, model: Bruker D8Advance). The test conditions were: Cu target Kα rays (λ=0.15406 nm), tube voltage 40 kV, tube current 40 mA, scanning range 2θ=10°~80°, scanning rate 5° / min, step size 0.02°. Thermal behavior analysis of the samples was performed using a differential scanning calorimeter (DSC, model: Netzsch DSC 214). The test conditions were: nitrogen atmosphere, heating rate 10℃ / min, test temperature range room temperature~1000℃, sample mass approximately 10 mg. Compressive strength and abrasion resistance of the particulate samples were tested using a universal tensile testing instrument (model: Instron 5969). Compressive strength test: Select particles with a diameter of 2~3 mm and perform a compression test at a loading rate of 2 mm / min. Test 10 particles for each sample and take the average value. Wear resistance test: Use a rotary drum wear tester. Put 50 g of particles with a diameter of 2~3 mm into the drum, rotate at 60 r / min, and wear for 30 min. Evaluate the wear resistance by the mass loss rate of the particles before and after wear. The lower the mass loss rate, the higher the wear resistance.

[0056] The particle size distribution of solid granular continuous casting flux prepared by disc granulation is significantly regulated by the content of composite binder, and the inhibitory effect of the composite binder on small particle agglomeration gradually increases with increasing content. Without composite binder (0%), the small particles of the flux are completely agglomerated, with effective particles only existing in the large particle size range of 316.23~2187.76 μm, with a peak particle size of 724.44 μm and a peak volume fraction of 14.49%, and the particle distribution is relatively dispersed. After adding 0.5% composite binder, only the large agglomerates are slightly broken up, and the effective particle size range shifts slightly downward to 275.42~1905.46 μm, with the peak particle size slightly reduced to 630.96 μm and a peak volume fraction of 14.75%, showing limited effect on particle size regulation. Specifically, as shown in the figure... Figure 4 As shown.

[0057] When the content of the composite binder increases to 1%, the agglomeration inhibition effect is significantly enhanced, and the effective particle size range expands considerably to 11.48~2187.76μm. A significant peak appears in the small particle size range (91.20μm, peak volume fraction 52.02%), and the particle system becomes dominated by small particles. Simultaneously, the particle size distribution width exhibits a "decreasing then increasing" trend; that is, it slightly decreases as the composite binder content increases from 0% to 0.5% (particle uniformity improves), and expands as it increases from 0.5% to 1%. However, at 1% content, it is a controllable distribution of "small particle size dominance + a small amount of large particle size coexisting," which is fundamentally different from the disordered wide distribution without composite binder. In summary, when using the disc granulation method, 1% composite binder can obtain a protective slag particle system dominated by small particles, 0.5% composite binder can balance a certain proportion of large particles with particle uniformity, and no composite binder easily forms large particle agglomerates.

[0058] Figure 5 OM and SEM images of samples with different composite binder contents are shown. The three SEM microstructure images of the solid granular protective slag prepared by disc granulation show high agreement with the particle size analysis data, clearly demonstrating the regulatory effect of the composite binder on the particle microstructure. The SEM image of the sample without composite binder (0%) is shown below. Figure 5 As shown in (a): the field of view is almost entirely composed of irregular large aggregates ranging from 316.23 to 2187.76 μm, with rough surfaces and blurred boundaries. No independent small particles are present, and the pores between the aggregates are large and disordered. This is consistent with the results in the particle size data where there is a signal only in the large particle size range, with a peak particle size of 724.44 μm, indicating that small particles have completely agglomerated into loose large particles due to a lack of dispersion. The SEM image of the sample with 0.5% composite binder content is shown below. Figure 5 As shown in (b): the number of large aggregates decreased slightly, and some aggregates showed slight dissociation at their edges. The effective particle size range shifted slightly downward to 275.42~1905.46 μm. Microscopically, large particles still predominated, but the surface was relatively dense, and the aggregate size became slightly more uniform. The peak particle size in the corresponding particle size data decreased slightly to 630.96 μm, and the peak volume fraction was 14.75%, indicating that the composite binder could only slightly break up the aggregates but could not form stable small particles. The SEM images of the sample with 1% composite binder content showed fundamental changes, such as... Figure 5(c) shows that the field of view is dominated by fine particles of 11.48~316.23μm, with the largest number of particles around 91.20μm (corresponding to 52.02% of the peak volume fraction in the particle size data). The small particles are nearly spherical, smooth, and uniformly dispersed, with only a small number of dense large particles of 316.23~2187.76μm scattered around, forming a composite microstructure of "small particles dominating + a small number of large particles dominating". This is completely consistent with the distribution characteristics of "small particle size significant peak + large particle size tail" in the particle size data, which confirms that 1% composite binder effectively inhibits the agglomeration of small particles through electrostatic stability and steric hindrance effect, while maintaining the structure of some large particles through bridging effect, thus achieving a controllable micromorphology. Therefore, SEM images visually verified the regulatory effect of composite binder content on the microstructure of the protective slag: without composite binder, the particles were severely agglomerated and loose; 0.5% composite binder slightly improved agglomeration, but large particles still dominated; 1% composite binder formed a uniformly dispersed system dominated by small particles, which was completely consistent with the particle size analysis results. In summary, the addition of composite binder can improve the morphology and structure of particles, and enhance their integrity and density. The improvement effect was optimal when the composite binder content was 0.5%.

[0059] The cross-sectional microstructure of the solid granular protective slag prepared by the disc granulation method, as observed by metallographic OM, is as follows: Figure 6 As shown, the effect of composite binder content on the internal structure of particles is clearly reflected, and the differences in the influence of different contents can be clearly identified by combining particle size analysis data. The OM cross-sectional diagram of the composite binder (0%) sample is shown below. Figure 6 As shown in (a): the particles have extremely poor internal density, with a large number of irregular pores. The pores are large in size and randomly distributed. The grains inside the particles are loosely bonded, with obvious grain dissociation gaps. This corresponds to the characteristics of large agglomerates in the particle size data of 316.23~2187.76μm. This indicates that without a binder, the grains cannot be effectively bonded during the particle forming process, resulting in a loose internal structure and many defects in the cross-section. The OM cross-section of the sample with 0.5% composite binder content is shown in the figure. Figure 6 As shown in (b): the number of internal pores is reduced compared to the case without binder, the pore size is slightly refined, the intergranular bonding state is slightly improved, and the internal compactness of the particles is slightly increased. However, local concentrated pores still exist, corresponding to a slight downward shift in the effective particle size range to 275.42~1905.46 μm in the particle size data. This indicates that low binder content can only initially improve the bonding effect of particle formation, and has limited effect on optimizing the internal microstructure. The OM cross-sectional diagram of the sample with 1% composite binder content shows a significantly optimized internal structure, such as... Figure 6As shown in (c), the internal density of the particles is significantly improved, with only a small number of uniformly refined micropores distributed. The grains are tightly bonded with no obvious dissociation gaps, forming a continuous and regular internal structure. This is highly consistent with the characteristics of fine particles (11.48~316.23μm) dominating the particle size data (peak volume fraction of 52.02% at 91.20μm), confirming that 1% composite binder achieves effective bonding between grains through bridging, suppressing the generation and aggregation of a large number of pores during the forming process, and simultaneously refining the particle size while optimizing the internal bonding state. In summary, the OM cross-sectional observation directly verifies the regulation law of composite binder content on the internal microstructure of protective slag particles: without composite binder, the particles are loose and the pores are disordered; 0.5% composite binder slightly improves the density but the optimization is limited; 1% composite binder can significantly improve the internal structure, obtaining a dense, tightly bonded, high-quality cross-sectional structure, and this law is completely consistent with the particle size distribution characteristics reflected by particle size analysis.

[0060] In summary, this invention has developed a composite binder system suitable for high-density protective slag and, for the first time, applied vibration-assisted technology to protective slag disc granulation. The granules were prepared through a multi-stage disc granulation process combined with vibration-assisted densification technology, achieving an integrated continuous production process of granulation, densification, and drying. Based on this process, protective slag particles with low porosity (<5%), particle size of 0.2-0.5 mm, high mechanical strength (>20 N / particle), and excellent melting uniformity were produced. The melting uniformity can reach ±1.5℃, and the dust generation is <0.1%. When the prepared protective slag particles are used in the continuous casting process of steel, their solid structure makes heat conduction more uniform, avoiding local overheating or incomplete melting, significantly reducing surface cracks of the billet, enabling the liquid slag layer thickness fluctuation to be less than 0.5 mm, reducing the surface crack rate of the billet by more than 60%, increasing the inclusion adsorption efficiency by 15%, and increasing the raw material utilization rate to 98%. It has significant economic benefits and environmental advantages, effectively overcoming various defects of existing technologies, and is particularly suitable for the continuous casting production of high value-added steel grades such as automotive steel and silicon steel, with significant industrial application value.

[0061] The technical solution provided by this invention has been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this invention. The descriptions of the embodiments above are only for the purpose of helping to understand the method and core ideas of this invention. It should be noted that those skilled in the art can make several improvements and modifications to this invention without departing from the principles of this invention, and these improvements and modifications also fall within the protection scope of the claims of this invention.

Claims

1. A method for preparing a solid granular continuous casting protective slag, characterized in that, Includes the following steps: Step 1: Mix the protective slag base material with the composite binder; The composite binder comprises: 0.5-1 wt% starch paste, 0.5-1.5 wt% sodium carboxymethyl cellulose, and 0.5-1 wt% polyvinyl alcohol; Step 2: Perform multi-stage granulation using a disc granulator; Step 3: Perform step-by-step drying on the particles obtained in Step 2 to obtain solid particle continuous casting protective slag with the required moisture content.

2. The method for preparing solid granular continuous casting protective slag according to claim 1, characterized in that: The protective slag base material includes 50-70 wt% wollastonite, 20-30 wt% blast furnace slag, 12-15 wt% fluorite, and the remainder is quartz sand.

3. The method for preparing solid granular continuous casting protective slag according to claim 1, characterized in that: The composite binder comprises 0.5-0.8 wt% starch paste, 1.5 wt% sodium carboxymethyl cellulose, and 0.8 wt% polyvinyl alcohol.

4. The method for preparing solid granular continuous casting protective slag according to claim 1, characterized in that: The specific process of multi-stage granulation using a disc granulator in step 2 is as follows: Pre-wetting stage: Disc tilt angle 40-45°, rotation speed 10-12 rpm, spray in 30% composite adhesive; Nucleus generation stage: Maintain an inclination angle of 45° and a rotation speed of 12-15 rpm to increase the particle diameter to 1-2 mm; Densification stage: Adjust the tilt angle to 50-55°, rotate the speed to 18-20 rpm, apply mechanical vibration at a frequency of 50-60 Hz simultaneously, and spray in the remaining composite adhesive.

5. The method for preparing solid granular continuous casting protective slag according to claim 4, characterized in that: The diameter of the disc granulator is 2-3m, and the frequency of the mechanical vibration is 55Hz.

6. The method for preparing solid granular continuous casting protective slag according to claim 1, characterized in that: The solid granular continuous casting protective slag has a porosity of <5% and a compressive strength of >20N / particle.

7. The method for preparing solid granular continuous casting protective slag according to claim 1, characterized in that: The solid granular continuous casting protective slag has a moisture content of <0.5%, a melting uniformity of ±1.5℃, and a dust generation of <0.1%.

8. A system for preparing solid granular continuous casting mold flux for implementing the method of any one of claims 1-7, characterized in that: include: A mixing device is used to mix the protective slag base material with a composite binder, said composite binder comprising: 0.5-1 wt% starch paste, 0.5-1.5 wt% sodium carboxymethyl cellulose, and 0.5-1 wt% polyvinyl alcohol; Disc granulators are used for multi-stage granulation of protective slag base materials with mixed composite binders; An auxiliary vibration device is used to provide mechanical vibration at a frequency of 50-60Hz during the granulation process of a disc granulator to assist in densification. Drying equipment is used to perform step drying on particles obtained by a disc granulator to obtain solid particle continuous casting protective slag with a moisture content that meets the requirements.

9. A solid granular continuous casting protective slag, characterized in that: It is prepared using the method described in any one of claims 1-7 or the preparation system described in claim 8.

10. The application of a solid granular continuous casting mold flux in the steel continuous casting process, characterized in that: The solid granular continuous casting protective slag is prepared by the method described in any one of claims 1-7 or the preparation system described in claim 8.